PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PBL BERBANTU APLIKASI CANVA DI KELAS V SD - Annisa Setiyana; Ika Septiana; Miyarti Miyarti (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This study aims to improve the learning outcomes of fifth grade students of SD 6 Hadipolo Kudus on Theme 1 Animal and Human Movement Organs through the Problem Based Learning (PBL) model assisted by the Canva application media. The research method applied is classroom action research. The results showed that the students' learning mastery had increased in every aspect. Cognitive aspects experienced an increase in the first cycle of 73.08%, the second cycle of 84.62%, and the third cycle 92.31%. The affective aspect in the first cycle is 80.76% for spiritual and 69.23% for social, in the second cycle 88.46% for spiritual and 100% for social, and in the third cycle 100% for spiritual and 100% for social. The psychomotor aspects in the first cycle in the content of science, Indonesian, and SBdP lessons are 79.81; 77.24, and 81.73. In cycle II, the content of science, Indonesian, and SBdP lessons, respectively, is 83.97; 83.65, 83.33. While in cycle III, the contents of science, Indonesian, and SBdP are 88.14; 87.18 and 88.14. The conclusion of the study is that the use of the Canva Application-Assisted PBL Model Can Improve Learning Outcomes.